Financing health care and the development prospects of private health insurance in Poland - Iwona Laskowska (Economic and Environmental Studies (E&ES), 2018)
Polish legislation names the general health insurance system as the main source of health care funding. Public health care funding in Poland is relatively small compared with other European countries, which restricts population's access to medical services and exposes the health care system to constant criticism (the Euro Health Consumer Index, 2017). The rising demand for health care and medical services, driven by demographic and technological factors as well as by changing expectations towards the services standard, is another reason why a search for alternative sources of health care funding seems inevitable. It is viewed that one of the solutions that might facilitate the functioning of the Polish health care system is private health insurance that could become a major element of national health care policy and provide the health care system with extra funding. The article presents some aspects of health care funding in Poland that are likely to increase interest in private health insurance and outlines the level of development of this insurance sub-market using the selected statistics (the number of insured persons, gross written premiums). The article has been prepared based on data provided by the Central Statistical Office, the Polish Insurance Association and Eurostat.
Keywords: I13; I18; 330; health care; funding; private health insurance